Semantic Change of the Word /khraj2/ ‘to love, to like’ in Thai - Iamsa-ard, Arbhon; Yuttapongtada, Methawee; Pimpuang, Kowit (มนุษยสังคมสาร (มสส.) คณะมนุษยศาสตร์และสังคมศาสตร์ มหาวิทยาลัยราชภัฏบุรีรัมย์, 2020)
The purpose of this study was to study the semantic change of the word /khraj2/ from Sukhothai to 2018 A.D. The Collected data were divided into 6 periods namely; 1) Sukhothai 2) Ayutthaya 3) the reign of King Rama I – III 4) the reign of King Rama IV - V 5) the reign of King Rama VI - VIII and 6) the reign of King Rama IX - 2018 A.D. The data were based on published documents from 1283 to 2018 A.D. The study revealed that /khraj2/ is defined into 4 meaning: 1) ‘to love, to like’ 2) ‘to want, to desire’ 3) ‘to think, to cogitate, to examine’ and 4) ‘not, not all’. Other major 3 meanings at first were found since Sukhothai period. Meaning ‘to love, to like’ gradually changed to a negative sexual semantic feature. Meaning ‘to want, to desire’ could be used for polite requests and official documents at the reign of King Rama IX period. However, meaning ‘to think, to cogitate, to examine’ had the least semantic change. Meaning ‘not, not all’ appeared in / maj2khraj2/ since the reign of King Rama I period and it had functioned similarly to negative marker.